Efficacy of infection control pathway in reducing postoperative infections in patients undergoing neurosurgery - Chunli Dong; Haozheng Yuan; Renyan Xu; Hui Zhang; Lili He; Weihong Qi; Xin Zhang (Journal of Infection in Developing Countries)
Introduction: The environment of the operating room (OR) is closely related to the postoperative complications of patients, and it is necessary to study, to what extent, the stringent management of the OR can reduce postoperative complications.